R. D. Orlova’s "Saroyan’s Dramaturgy" Unpublished Article - GUDKOV, MAKSIM (Bulletin of Yerevan University H: Russian Philology, 2021)
Тhe reader is introduced to yet unpublished critical essay on William Saroyan’s dramaturgy written by the authority in American literature R.Orlova. This text was written as introduction for a collection of Saroyn’s plays, by the order of Moscaw publishing house “Iskusstvo”, but it did not appear in the collection, on some reasons.